Evaluation of the Implementation Process of the Batik Curriculum for Deaf Children as a Support Effort to Increase Student Independence - Cantika, Varary Mechwafanitiara; Kailani, Rizal; Kusweni, Rina (Universitas Negeri Semarang, 2023)
The life skills curriculum is one of the curricula initiated to bring out the independence of deaf children. One of the areas of life skills taught to deaf children in Indonesia is batik life skills. This research aims to describe the evaluation of implementing the batik curriculum for deaf children as a support for increasing student independence. This descriptive evaluation research uses a case study design and a qualitative approach. The evaluation model used is the CIPP evaluation model, which is limited to process components. Data collection in this research was carried out by interviewing one of the batik teachers at SLB Negeri Seduri Mojosari Mojokerto. Interview questions were based on research instruments and evaluation criteria. Data analysis in this research uses interactive model analysis. The results in this study were also tested for the validity of the data. In general, the research results show that implementing the batik life skills curriculum, which was reviewed as an effort to increase the independence of deaf children, showed promising results. These good results are viewed from the objectives, learning materials, materials, methods, media, and learning evaluations the teacher implements.